Non-destructive on-chip cell sorting system with real-time microscopic image processing - Ichiki Takanori; Suzuki Ikurou; Hattori Akihiro; Takahashi Kazunori; Yasuda Kenji (Journal of Nanobiotechnology, 2004)
Abstract Studying cell functions for cellomics studies often requires the use of purified individual cells from mixtures of various kinds of cells. We have developed a new non-destructive on-chip cell sorting system for single cell based cultivation, by exploiting the advantage of microfluidics and electrostatic force. The system consists of the following two parts: a cell sorting chip made of poly-dimethylsiloxane (PDMS) on a 0.2-mm-thick glass slide, and an image analysis system with a phase-contrast/fluorescence microscope. The unique features of our system include (i) identification of a target from sample cells is achieved by comparison of the 0.2-μm-resolution phase-contrast and fluorescence images of cells in the microchannel every 1/30 s; (ii) non-destructive sorting of target cells in a laminar flow by application of electrostatic repulsion force for removing unrequited cells from the one laminar flow to the other; (iii) the use of agar gel for electrodes in order to minimize the effect on cells by electrochemical reactions of electrodes, and (iv) pre-filter, which was fabricated within the channel for removal of dust contained in a sample solution from tissue extracts. The sorting chip is capable of continuous operation and we have purified more than ten thousand cells for cultivation without damaging them. Our design has proved to be very efficient and suitable for the routine use in cell purification experiments.